PENGARUH KUALITAS PELAYANAN KTP ELEKTRONIK TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN TANDES SURABAYA - Zainul Lutfi (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study was to analyze the effect of the quality of electronic KTP services on community satisfaction at the Tandes District office, Surabaya. This study uses a quantitative approach. The population in this study is the community of applicants for Electronic KTPs at the Tandes District Office, with an average of 162 applicants per month. While in this study using non-probability sampling technique with the type of accidental sampling, the sample used was 95 respondents. The results of the study show that partially the significant influence of the independent variables consisting of Reliability, Reliability, Responsiveness, Assurance and Empathy on satisfaction, namely the people in Tandes sub-district, Surabaya. The variable that has the most influence on the variable level of community satisfaction is Responsiveness.